283 Relationship between Aeroallergen Sensitization and Asthma Severity in Patients with Aspirin-Exacerbated Respiratory Disease - Mitsui, Chihiro (World Allergy Organization Journal, 2012)
BACKGROUND: The pathogenesis of aspirin-exacerbated respiratory disease (AERD) is presumed to involve the aspirin/non steroidal anti-inflammatory drug (NSAID)-induced abnormal metabolism of arachidonic acid, resulting in the production of 5-lipoxygenase metabolites, particularly leukotriene C4. Aspirin intolerance occurs around the same time as asthma onset, and a few of the patients with AERD had suffered from pediatric asthma. Although atopy is not associated with the pathogenesis of AERD, some of the patients with AERD have aeroallergen sensitization. There are few studies in which the association between the pathogenesis of AERD and atopy has been clarified. METHODS: Ninety AERD patients, whose aspirin sensitivity was determined by the aspirin challenge test, and 100 aspirin-tolerant asthma (ATA) patients, whose age and sex were adjusted, participated in this study. Atopy was defined as a positive reaction in an intradermal test to one or more of 19 common aeroallergens, or a positive reaction above class one in Immuno CAP RAST. We analyzed the relationships between aeroallergen sensitization and clinical settings of AERD patients. RESULTS: The atopic and non atopic AERD groups showed median serum total IgE concentrations of 464 and 130 IU/l (P value = 0.004), respectively. The asthma of atopic patients with AERD was milder than that of non atopic patients with AERD. (P value = 0.05) The Lund-Mackay score of atopic patients with AERD was lower than that of non atopic patients with AERD. (P value = 0.02) CONCLUSIONS: Two-thirds of the patients with AERD showed aeroallergen sensitization. The asthma and sinusitis in atopic patients with AERD were significantly milder than those in non atopic patients with AERD. Aeroallergen sensitization might prevent the worsening of asthma in patients with AERD.